Portfolio Manager Compensation in the U.S. Mutual Fund Industry - Ma, Linlin (Institutional Knowledge at Singapore Management University, 2013)
Using a unique hand-collected dataset of over 4,000 mutual funds, we study the compensation structures of individual portfolio managers in the U.S. mutual fund industry. About three-quarters of the portfolio managers in our sample receive performance-linked pay from investment advisors. Managers with performance-based compensation exhibit superior fund performance, especially when advisors link pay to performance over longer time periods. By contrast, we do not find that alternative compensation arrangements such as pay linked to fund assets or advisor profits are associated with better fund performance. Performance-linked pay is more prevalent among larger investment advisors, non-stakeholder portfolio managers, portfolio management teams, and in-house managed funds. Overall, our study provides novel empirical evidence on portfolio manager compensation in the mutual fund industry.